ANALYSIS OF OPPORTUNITIES FOR UNMANNED AIRCRAFT SYSTEMS APPLICATION IN THE CIVIL FIELD - Харченко, В.; Прусов, Д. (Proceedings of National Aviation University (archive), 2012)
The principal directions of unmanned aircraft systems application in the civil field have been consideredtaking into account the development of aviation industry sectors, the available aircraft engineering andaerospace industry potential, and prospects for production and operation of unmanned aircraft systems. Theconcept of creation and organization of civil unmanned aircraft systems has been analyzed depending on themission orientation, and considering wide range of issues concerning the use of the available potential for thedesign, manufacture and operation. The principles of economic feasibility and effectiveness of differenttypes of unmanned aircraft systems in the civil field have been considered and their subsequent integrationinto the common airspace due to the necessity of solving diverse problems of conceptual, technical,technological, methodological, institutional and regulatory developments.